Highly Manufacturable Deep (Sub‐Millimeter) Etching Enabled High Aspect Ratio Complex Geometry Lego‐Like Silicon Electronics. Issue 16 (1st February 2017) - Ghoneim, Mohamed Tarek; Hussain, Muhammad Mustafa
Abstract : A highly manufacturable deep reactive ion etching based process involving a hybrid soft/hard mask process technology shows high aspect ratio complex geometry Lego‐like silicon electronics formation enabling free‐form (physically flexible, stretchable, and reconfigurable) electronic systems.